Understanding the cooling capacity and its potential drivers in urban forests at the single tree and cluster scales. (June 2023) - Wang, Chengcong; Ren, Zhibin; Chang, Xinyue; Wang, Guodong; Hong, Xu; Dong, Yulin; Guo, Yujie; Zhang, Peng; Ma, Zijun; Wang, Wenjie
Highlight: Unmanned aerial vehicle image can be used well for tree species classification. The cooling intensity of trees varied greatly ranging from 5.05 °C to 16.12 °C. The tree canopy coverage threshold (40%) was determined for affecting cooling intensity. The spatial distribution of tree species had significant impact on the cooling intensity. Our founding could be used for the design of urban forest for maximizing cooling service. Abstract: Urban forests can mitigate the urban heat island effect by serving as cooling islands. However, urban forest cooling potentials and their influencing factors at the single tree and cluster scales remain unclear. In our study, unmanned aerial vehicle image with very high resolution (5 cm) was used to classify tree species, assess the cooling intensities of different tree species, and ascertain their drivers at single tree and cluster scales. Our results indicate that, unmanned aerial vehicle images can be used well for tree species classification with the accuracy of approximately 87%. We found the different cooling intensities for different tree species, ranging from 5.05 °C to 16.12 °C, with an average value of 11.2 °C. Trees have 1.35 °C higher cooling intensity than shrubs. At single tree scale, the main factors for affecting the cooling intensity were tree height and crown thickness. When tree height increased by 1.82 m or crown thickness increased by 1.3 m, the cooling intensity increased by 0.5 °C. At cluster scale, we found that the cooling intensity does not increase more with increasing tree canopy coverage when the canopy coverage was larger than 40%. In addition, we found that urban forest cooling intensity was positively correlated with the connectivity and contagion of trees at the cluster scale, and the relationship of cooling intensity with diversity conformed to a V-shaped curve. This study could be helpful for the construction and planning of urban forests to handle urban heat waves. Graphical abstract: Image, graphical abstract